How does starch affect the sensory characteristics of mazamorra morada? A study with a dessert widely consumed by Peruvians - Saldaña E. (2018)
Erick Saldaña received the support of the “Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica - CONCYTEC" from Perú (CIENCIACTIVA programme, PhD scholarship contract agreement No. 104-2016-FONDECYT).